2007
DOI: 10.1002/he.258
|View full text |Cite
|
Sign up to set email alerts
|

From Baccalaureate to the professoriate: Cooperating to increase access to graduate education

Abstract: Faculty in the Summer Research Opportunities Program mentor and prepare students for graduate school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Researchers have also studied the benefits of undergraduate research programs (Allen & Zepeda, 2007;Barlow & Villarejo, 2004;Carter, Mandell, & Maton, 2009;Chatman, 2005;Eagan, et al2010;Hathaway, Nagda, & Gregerman, 2002;Maton & Hrabowski, 2004;Seymour, Hunter, Laursen, & DeAntoni, 2004). In particular, some research has demonstrated that such programs may increase students' decision to pursue post-baccalaureate studies.…”
Section: Student Research Opportunitiesmentioning
confidence: 99%
“…Researchers have also studied the benefits of undergraduate research programs (Allen & Zepeda, 2007;Barlow & Villarejo, 2004;Carter, Mandell, & Maton, 2009;Chatman, 2005;Eagan, et al2010;Hathaway, Nagda, & Gregerman, 2002;Maton & Hrabowski, 2004;Seymour, Hunter, Laursen, & DeAntoni, 2004). In particular, some research has demonstrated that such programs may increase students' decision to pursue post-baccalaureate studies.…”
Section: Student Research Opportunitiesmentioning
confidence: 99%
“…Pottinger (1989) reported that attrition rates at four-year institutions for students living on the reservation were over 75 percent. Latino attrition is also extremely high (Mcfadden & Zepeda, 2007). Although students who complete a bachelor's degree represent a special group who have overcome many obstacles to education that often affect ethnic groups (e.g., transportation, adequate undergraduate experiences, financial needs), these challenges do not go away in graduate school.…”
Section: Recruitment and Retention And Mentoringmentioning
confidence: 99%